2016
DOI: 10.1111/1744-7917.12321
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cold on the immune system of burying beetle, Nicrophorus vespilloides (Coleoptera: Silphidae)

Abstract: Insect overwintering is one of the most astonishing phases of the insect life cycle. Despite vast amounts of knowledge available about the physiological mechanisms of this phenomenon, the impact of stress factors on insect immune system functioning during the winter is still unknown. The aim of this study is to analyze how low temperatures influence the immune system of the beetle Nicrophorus vespilloides. The results show that the beetle's immune system is differently modulated by cold induced in laboratory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…Nicrophorus vespilloides beetles were cultured at the Department of Animal Physiology and Development, Faculty of Biology AMU, according to a method previously described by Urbański et al (2014Urbański et al ( , 2017 under stable conditions similar to conditions characteristic of summer in northern Poland (21°C, 15 h light : 9 h dark). The beetles were kept in separate plastic containers and were fed meat twice a week.…”
Section: Insectsmentioning
confidence: 99%
“…Nicrophorus vespilloides beetles were cultured at the Department of Animal Physiology and Development, Faculty of Biology AMU, according to a method previously described by Urbański et al (2014Urbański et al ( , 2017 under stable conditions similar to conditions characteristic of summer in northern Poland (21°C, 15 h light : 9 h dark). The beetles were kept in separate plastic containers and were fed meat twice a week.…”
Section: Insectsmentioning
confidence: 99%
“…The two most numerous types of hemocytes were plasmatocytes and granulocytes. The first group is the predominant group in most insects, as was observed for example in beetles Carabus lefebvrei 55 , N. vespilloides 47 and the fly Simulium vittatum 72 . In turn, the latter group, granulocytes, participate in basic mechanisms of cellular response and in hemolymph clotting, wound healing and necrotic cell phagocytosis 70 , 73 75 .…”
Section: Discussionmentioning
confidence: 79%
“…Yi and Lee 67 showed that the number of hemocytes in Eurosta solidaginis was reduced by 40% under extremely low temperatures (− 80 °C), which in turn decreased the activity of the cellular response. In Coccus hesperidum, cold stress leads to a decrease in the encapsulation ratio 68 , whereas in Nicrophorus vespilloides, cold stress causes a gradual decrease in the number of circulating hemocytes during winter 47 . Additionally, it was shown that cold stress decreases the number of phagocytic cells in diapausing pupae of Samia cynthia pryeri 69 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, cold stress can lead to changes in immune system activity. Some immune system variables that can be affected by cold in the burring beetle Nicrophorus vespilloides include total haemocyte count, phenoloxidase activity, and the phagocytic ability of haemocytes [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%